Endotherapic treatment to control Toumeyella parvicornis Cockerell infestations on Pinus pinea L. Issue 6 (4th April 2022) - Di Sora, Nicolò; Rossini, Luca; Contarini, Mario; Chiarot, Enrico; Speranza, Stefano
Abstract: BACKGROUND: The pine tortoise scale, Toumeyella parvicornis (Cockerell, 1897), is a damaging insect pest native to North America. Its accidental introduction into Europe, where it was first reported in central‐southern Italy, is leading to severe infestations among stone pine trees, Pinus pinea L. causing severe infestations and generating a major risk to the health and safety of the citizens as well. This preliminary study aimed at finding an effective low‐impact control strategy against Toumeyella parvicornis . We evaluated the effect of endotherapic abamectin injected into infested stone pines in the Parco Archeologico di Ostia Antica (Rome). RESULTS: Results showed that endotherapic abamectin significantly reduced the pine tortoise adult female populations and had a persistence into plants of approximately 60 days. The first trace of abamectin on the plant's crown was detected 1 month after the treatment. Moreover, the survey highlighted a higher presence of the pest on the twigs of the plants than on needles. CONCLUSIONS: These findings offer an important tool in fighting the damaging activity of this phytophagous, especially in an urban context where interventions with treatments are strictly regulated by national laws. Endotherapy, in fact, would reduce the dispersion of active ingredients by drift, an aspect that could represent a valid alternative to manage plants in public areas. Given the actual lack of scientific information about other control solutions, abamectin endotherapic treatments would be the more effective strategy currently applicable. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Abamectin insecticide through endotherapy treatment, is effective to control Toumeyella parvicornis affecting Pinus pinea . The effect of the product starts 45 days after the treatment with a persistence of 60 days.